Pain during Cast Wedging of Forearm Shaft and Distal Forearm Fractures in Children Aged 3 to 12 Years-A Prospective, Observational Study - Florian Freislederer; Tobias Berberich; Thomas O. Erb; Johannes Mayr (MDPI AG, 2020)
Background: Although fracture displacement in children is easily treated by cast wedging, no data on pain associated with the procedure are available. We hypothesized that there is no clinically relevant difference in pain before and after cast wedging in children between 3 and 12 years of age. Patients and Methods: This international, multicenter, prospective, observational study included 68 children (39 male, 29 female) aged 3 to 12 years (median age 8 years) with forearm fractures. Cast wedging was performed 5 to 10 days after the injury. Before starting the procedure, we administered a single oral dose of sodium metamizole (10 mg/kg body weight), and the children inhaled a nitrous oxide/oxygen mixture (50%/50%) during the wedging procedure. Pain was rated on a visual analog scale (VAS) 5 to 10 min before incision of the cast as well as 3 to 5 min and 30 min (maximum remembered pain) after inhalation stop. The degree of bending was judged either by the surgeon or was determined on the basis of first signs of pain expressed by the patient. We assessed the effectiveness of the procedure by obtaining X-ray images in two planes after 3 to 9 days. Results: Among the 68 patients, median VAS score before cast wedging was 0. This increased to a score of 1 (p = 0.015) at 3 to 5 min after the procedure. Median VAS score for the maximum remembered pain measured after 30 min was 0. Median differences in angulation between proximal and distal bone fragments before and after the intervention were 0° (p < 0.0001) in the a.p. view and 8.4° (p < 0.0001) in the lateral view. Conclusion: Cast wedging improved the position of forearm fracture fragments at the expense of minimal short-term pain.